If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16c + 24d = 0 Solving 16c + 24d = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-24d' to each side of the equation. 16c + 24d + -24d = 0 + -24d Combine like terms: 24d + -24d = 0 16c + 0 = 0 + -24d 16c = 0 + -24d Remove the zero: 16c = -24d Divide each side by '16'. c = -1.5d Simplifying c = -1.5d
| k^2-20/18 | | -11+n^15=-1 | | 3*(x+2)-5*(x+3)=1 | | -5+t/2=14 | | (x-9)+(x+5)=90 | | 3.5y=y+7+2 | | d/3+10=14 | | 12x5/5x11 | | x/4+6=4 | | 2.8y=y+6+2 | | 8x-117=4x-9 | | 95-2x=34x+19 | | 5+3(-4)=7(-4+3) | | 6x-5x+2x= | | -17-4x=11-8 | | 3.65=X*10 | | 15x-23=10x+27 | | -21/7= | | 3.5y=y+3+2 | | 5/9+2x=2/3 | | -2x+15=4x+51 | | 20f+(-8-15)=3(4f-5) | | 2.7y=y+3+2 | | 4x-7=-2x+23 | | 6x+9=8x+16 | | 3+1x/4=-5/16 | | 5x+25=15 | | a/22-4.5+2a=7/11+17a/11+4/11 | | 6x-6=12x-42 | | 2/5+x=1/8 | | 2(y-3)=5 | | 6x/2-3x-4/2-3x-2x=0 |